2021
DOI: 10.1016/j.psj.2021.101175
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of crude chalaza hydrolysates against liver fibrogenesis via antioxidation, anti-inflammation/anti-fibrogenesis, and apoptosis promotion of damaged hepatocytes

Abstract: Four-hundred metric-ton chalazae are produced annually from the liquid-egg processing and always cause a heavy burden due to handling cost in Taiwan. After chalazae were hydrolyzed by protease A, the amounts of hydrophobic, aromatic, and branched-chain amino acids, as well as anserine were dramatically increased. This study was to understand the antifibrogenic effects of protease A-digested crude chalaza hydrolysates ( CCH-As ) on livers of thioacetamide ( TAA ) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…The growth performance, serum biochemical values, proinflammatory cytokine content, oxidative stress status, and histological observation suggest that a dose of 100 mg TAA kg −1 BW 3 times a week for 8 weeks induces liver fibrogenesis in rats, similar to prior reports 2,18 . Rats intoxicated with TAA during liver fibrogenesis had larger liver weight or size and worse liver damage indices (higher AST, ALT, and ALP levels).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The growth performance, serum biochemical values, proinflammatory cytokine content, oxidative stress status, and histological observation suggest that a dose of 100 mg TAA kg −1 BW 3 times a week for 8 weeks induces liver fibrogenesis in rats, similar to prior reports 2,18 . Rats intoxicated with TAA during liver fibrogenesis had larger liver weight or size and worse liver damage indices (higher AST, ALT, and ALP levels).…”
Section: Discussionsupporting
confidence: 80%
“…35 Our in vitro data suggest that the LJWES pretreatment can week for 8 weeks induces liver fibrogenesis in rats, similar to prior reports. 2,18 Rats intoxicated with TAA during liver fibrogenesis had larger liver weight or size and worse liver damage indices (higher AST, ALT, and ALP levels). These rats also had abnormal lipid metabolism in the liver, including reduced production and delivery efficiencies of apoprotein B and low-density lipoprotein and accumulation of microsomal sphingomyelin that alters membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings here reported revealed among the medwakh smoker group an increased level of metabolites linked with inflammatory mechanism, such as pyroglutamic acid 23 , 24 , deoxyguanosine 25 and anserine 26 . In order to investigate futher an eventual association of metwakh smoking and inflammation, we decided to measure CRP, a widely known clinical indicator of inflammatory conditions 27 , 28 .…”
Section: Resultssupporting
confidence: 56%
“…fertilizer or incineration. Recently, food-derived protein hydrolysates have been demonstrated to own several biofunctionalities like antioxidant, 4 cardioprotection, [5][6][7] hepatoprotection, [8][9][10] reproductive function, 11 and antihypertension 12 etc. It has been reported that biofunctionalities of protein hydrolysates or peptides mainly result from their amino acid composition or peptides with specific sequences and structures.…”
mentioning
confidence: 99%